Analysis of a capacity-based redispatch mechanism - Karl-Martin Ehrhart; Anselm Eicke; Lion Hirth; Fabian Ocker; Marion Ott; Ingmar Schlecht; Runxi Wang (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This paper discusses a capacity-based redispatch mechanism in which awarded market participants are compensated for their availability for redispatch, rather than activation. The rationale is to develop a market design that prevents so-called 'inc-dec gaming' when including flexible consumers with a market-based approach. We conduct a game-theoretical analysis of a capacity-based redispatch mechanism. Our analysis reveals that despite its intention, the capacity-based redispatch is prone to undesirable behavior of market participants. The reason is that the availability payment incentivizes participants to change their energy consumption (generation) behavior. However, this also applies to undesired participants who increase the redispatch requirement through participation. Under certain assumptions, the additional redispatch potential equals the additional redispatch demand it creates. Consequently, the mechanism does not resolve network constraints, while causing costs for the compensation payments. Furthermore, we study three alternative implementation options, none of which resolves the underlying problem. It follows from our analysis that a mechanism can only be promising if it is capable to distinguish between the potential participants to exclude the undesirable ones.
Keywords: D43; D44; L13; Q41; Q48; 330; Energy market; Congestion management; Capacity-based redispatch; Game theory; Auctions